Acceptance of Ar Rahnu among Women Entrepreneurs in Kelantan - Amni Mohd Adnan (2018)
The rapid development of the economy in this country attracts more women to actively engage in the entrepreneurial world. Many women entrepreneurs become millionaires and some of them more aggressive than men in term of their thoughts, feelings and actions Micro-enterprise are playing an increasing role in the Malaysia economy. Although micro-enterprise always gives positive impact to Malaysia economy, they also have their own problem to obtain their funding of capital. In 1983, Ar Rahnu was introducing as an alternative for the Muslim community to use Islamic system that suits the shariah needs and requirements. It shows that Ar Rahnu can help women entrepreneurs to obtain funding. This research is study on the acceptance of Ar Rahnu among women entrepreneurs in Kelantan. This research is to study the knowledge, commitment and the effort that will influence the acceptance of Ar Rahnu among women entrepreneurs in Kelantan.